Effects of Fuel Subsidy Removal on Socioeconomic Status of the Inhabitants of Northeast Nigeria - Usman Sambo; Kachalla Bura Lumami (Department of Public Administration, 2025)
Subsidising fuel and other essential commodities that are unaffordable for the poor and disadvantaged is a component of social security and welfare policies in many countries. However, these subsidies come at a significant cost, consuming a large portion of budgets intended for infrastructure development. This has sparked debates about the feasibility of maintaining subsidies or abolishing them. Nigeria, one of the largest oil-producing countries in the world, has subsidised fuel for many decades to ensure affordability. However, allegations of corruption and concerns about the opportunity costs of subsidising fuel have raised issues, while projections of severe hardship following subsidy removal continue to warn policymakers. This study therefore examines the implications of subsidy removal in 2023 on the socioeconomic status of residents in Northeast Nigeria. Data were collected through multi-level cluster sampling using structured questionnaires and in-depth informant interviews with unstructured questionnaires, in addition to consulting existing documents. The collected data were discussed, analysed, and interpreted using statistical tools in non-automated SPSS and qualitative interview discussions. The study found that subsidy removal caused severe suffering and unprecedented hardship for the inhabitants of the Northeast. Therefore, the study recommends, among other measures, that the government should revise its haphazard subsidy removal and intensify social security transfers to the poor.